Ocean Buoy for Energy Production: Short Comments on Its Irregular Behavior - Ribeiro, Mauricio A.; Tusset, Angelo M.; Lenz, Wagner B.; Balthazar, Jose M. [UNESP] (Springer Nature, 2022)
Purpose: We investigated the non-linear dynamic behavior of a system for energy production using ocean wave motion. The compound consists of a linear electromagnetic system coupled to a float to move under the action of marine waves. We define the equations of motion of the structure together and analyze the behavior of the parameters connected to the non-linear spring. Therefore, we analyzed the behavior of the average power for the parameters linked to the wave profile, the resistance of the electromechanical motor, and the non-linearity parameters related to the damping coming from a cubic spring considered to the system. Methods: The analyze of non-linear dynamic behavior through the analysis of set parameter (load resistance and non-linear spring constant) by the Maximum Lyapunov exponent, other analyses performed were employing bifurcation diagrams, phase portraits, and Poincaré maps. Results: As a result, we obtain the regions where there is a chaotic regime for load resistance and non-linear spring constant. The results also provide the behavior of energy production by the electromechanical motor system applied to an oceanic buoy. Conclusion: The investigation of the dynamics of an energy collection system by vibrations of oceanic waves corroborates the production of clean energy and thus analyzes the parametric behavior of the regions of maximum and minimum average power produced.
Keywords: Energy production; Nonlinear dynamics; Ocean wave